The impact of capital inflows on economic growth in Malawi: an asymmetric analysis - Zimba, Towani Mnyagala (School of Economics, 2026)
This study investigates the impact of four capital flows: external debt, official development assistance (ODA), remittances, and foreign direct investment (FDI)- on Malawi's economic growth using annual data spanning 1980 to 2022. Previous studies in the literature focus on a single capital flow and assume a symmetric relationship between capital flows and growth. However, this study focuses on how various capital flows each impact growth and considers potential asymmetry in capital flows' effects. The study determines asymmetric long-run and short-run relationships between capital flows and growth using a Nonlinear ARDL (NARDL), and the results are compared to the linear case using an Autoregressive Distributed Lag (ARDL) model. The NARDL models reveal significant asymmetries for all four capital flows, suggesting that positive and negative shocks influence growth disproportionately. In the long run, for all models, an increase in each capital flow increases growth, while reductions in inflows decrease growth, in some cases by a much larger proportion than the increase. In the short run, however, an increase in debt was detrimental to growth, yet debt and remittance inflow reduction improved growth. Conversely, an increase in FDI and remittances improved growth, while a decrease in FDI reduced growth. In contrast, the long-run ARDL results indicate that Remittances and ODA positively affect economic growth. Yet, external debt and FDI have no significant impact. In addition, short-run results show that lagged FDI and external debt positively impact growth, while ODA and remittance have no significant short-run effect. The study contributes to the literature by showing the disproportionate impact of positive and negative capital shocks on growth, which suggests that models that fail to account for asymmetry may be misspecified. These novel results show that accounting for asymmetric effects reveals dynamics that are overlooked in studies that assume that the capital growth nexus is symmetric.